PENGARUH MODAL, JUMLAH ANGGOTA DAN VOLUME USAHA TERHADAP SISA HASIL USAHA (SHU) PADA KOPERASI KARTIKA ACEH BARAT KABUPATEN ACEH BARAT - Raidayani Raidayani (Jurnal Bisnis Tani, 2018)
This research aims to examine the relationship of venture capital, the number of members, and the volume of cooperative efforts to the remaining business results in primary cooperative Kartika Makodim 0105 in West Aceh district. The data in this study used the time series of the period of 2011 to 2017 with a sample of cooperatives is the Primary Cooperative Kartika Makodim 0105 Aceh BArat. The analysis model used to measure the percentage of average increase of each independent variable to the remaining results of operation Kartika Primary Cooperative of West Aceh. The results showed that the business capital, the number of members, and the volume of business cooperative have influence  near the increase of a percentage to the rest of the cooperative business Primer Kartika in West Aceh District. It is expected that the Kartika Primary Cooperative in West Aceh will continue to increase the remaining business of cooperatives in West Aceh Regency, increasing the business capital of cooperatives in West Aceh, thus making cooperative performance more developed in its economic activities. Furthermore, it encourages TNI members to become cooperative members so as to increase the number of cooperative members. besides that policy makers should also continue to guide and guide the cooperative to increase the number of members and business volume. Thus, the Primary Cooperative Kartika Makodim 0105 in West Aceh can continue to be active in improving the SHU of West Aceh District.